PECULIARITIES OF THE HIGHER EDUCATION TRANSFORMATION IN THE PERIOD OF POSTPANDEMIA IN THE DIMENSION OF EUROPEAN RESEARCH - Melnyk, Natalia; Rogalska-Yablonska, Inna (Mountain School of Ukrainian Carpaty, 2021)
The article presents an analytical review of scientific research of Ukrainian and European scientists on the problem of transformation of higher education during the pandemic period and after its completion. The authors identify the main areas of research, their analysis. The authors' analytical review of the transformation of higher education in the Ukrainian and European dimensions during the pandemic and post-pandemic will highlight the following main areas: Ukrainian researchers focus on monitoring and identifying challenges, barriers, difficulties arising in the pandemic and its completion, as well as part of the research on the socio-emotional state of students and teachers; instead, Europeans are working to solve problems such as: the psychological problems of students and teachers during quarantine; the quality of higher education in terms of social distancing; features of the organization of the educational process in terms of distance education and improving the forms of interaction between students and teachers in order to ensure the same quality educational process; problems of diagnosing the positive and negative consequences of a pandemic and the forced social distancing caused by this pandemic. The main challenges for Ukrainian higher education institutions at the beginning of the pandemic were: methodological readiness of teachers to implement distance learning; for European university education, these were the search for improved forms of distance education and quality assurance. The study enables Ukrainian scientists working on overcoming challenges related to social distancing and loss of socio-emotional aspect of the educational process to build a vector of further ways and mechanisms to optimize the organization of higher education in the post-pandemic period, taking into account already implemented in European countries research and experience gained from the results of such research.